Analisis Metode Pembelajaran Bahasa Arab Di Madrasah Diniyah Al-Amiriyyah Blokagung - Ahmad Hasinur Rohman (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2022)
This study aims to identify and analyze the methods used in learning Arabic in grade 2 of Ula Madrasah Diniyyah Al-Amiriyyah Blokagung Karangdoro Tegalsari Banyuwangi for the 2020/2021 academic year. In its implementation, the researcher uses a qualitative approach with descriptive analysis. The samples used were Ula 2nd grade students, Arabic teacher, Assistant Head of Curriculum Madrasah and Head of Madrasah Diniyyah Al-Amiriyyah Blokagung Karangdoro Tegalsari Banyuwangi. Data collection carried out by researchers in the form of structured observations, in-depth interviews, documentation and triangulation to find the validity of the data obtained. The results of the study show that learning planning is classified as professional, because teachers always make learning implementation plans that have become their obligations. In carrying out the learning methods carried out by educators, namely the direct method and the group method. The media used is by using the Book of Madarisud Durusullughah Al-Arobiyyah. Broadly speaking, the evaluation is carried out in accordance with the learning objectives that have been set. The recommendation of this research is aimed at the Head of Madrasah Diniyah Al-Amiriyyah, Arabic learning materials should contain things that do not burden students in understanding the rules being taught and strengthen the material by increasing vocabulary and in preparing textbooks it is advisable to increase the number of pictures related to vocabulary. , so that students are enthusiastic to learn. For schools, regarding the problem of procuring learning resources, schools can seek cooperation or ask for help from the ministry of religion or other parties, add facilities that support learning methods or provide book rental facilities for students. For teachers, they should not give up in adding insight related to materials, methods, media and evaluation systems in order to support the smooth learning and achievement of Arabic language competence well. Readers should always continue to add insight about learning Arabic and keep trying to find something innovative for the sake of renewing Arabic learning in grade 2 Ula Madrasah Diniyyah Al-Amiriyyah Blokagung to be even better.